2006
DOI: 10.14411/eje.2006.051
|View full text |Cite
|
Sign up to set email alerts
|

Complex phenological responses to climate warming trends? Lessons from history

Abstract: Abstract. Responsiveness of Lepidoptera phenology to climate has been detected in a number of species during the current trend in global warming. There is still a question of whether climate signals would be evident in historical data. In this paper we examine the climatic response of 155 species of moths and butterflies collected during the period 1866-1884 in Wiltshire, southern England. In general, species responded to increased temperature in the previous October by delayed appearance and to increased temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 15 publications
2
20
1
Order By: Relevance
“…Butterflies and moths have been prominent in these studies as well-documented species that are sensitive to climate, both directly and indirectly, through impacts on host species (Dennis, 1993;Pollard & Greatorex-Davies, 1997;Parmesan et al, 1999;Hill et al, 2002;Hanski et al, 2004;Sparks et al, 2006;Powney et al, 2010;Srygley et al, 2010). Most studies of climate change influencing organisms utilise coarse-grained temperature and precipitation variables that are averaged at a seasonal or even annual scale (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Butterflies and moths have been prominent in these studies as well-documented species that are sensitive to climate, both directly and indirectly, through impacts on host species (Dennis, 1993;Pollard & Greatorex-Davies, 1997;Parmesan et al, 1999;Hill et al, 2002;Hanski et al, 2004;Sparks et al, 2006;Powney et al, 2010;Srygley et al, 2010). Most studies of climate change influencing organisms utilise coarse-grained temperature and precipitation variables that are averaged at a seasonal or even annual scale (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Second, do species respond in similar ways to patterns of interannual variation in weather? Given the diversity of species studied, an expectation of consistency of response to weather would be naive (Sparks et al 2006). Instead, we designed analyses to ask which weather variables are associated with a more or less consistent response across species.…”
Section: Introductionmentioning
confidence: 99%
“…At the broadest scale, latitude determines the climatic tolerances of species (Gutierrez & Menendez 1995;Dennis et al 2008), mainly because the time available in which to complete the life cycle is a primary constraint (Thomas 1993;Oliver et al 2009). Climate is of such importance that increases in temperature have been observed to increase range and distribution (Davies et al 2005;Lawson et al 2012), advance emergence dates (Roy & Sparks 2000;Sparks et al 2006) as well as increasing movement (Sparks et al 2005;Sparks et al 2007). However, relatively few studies have demonstrated the importance of temperature on abundance (Pollard 1988;Roy et al 2001), and so comprehending the link between temperature and population dynamics of individual species remains poorly understood (WallisDeVries et al 2011).…”
Section: Introductionmentioning
confidence: 99%